2006
DOI: 10.1097/01.aud.0000224100.30525.ab
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Neuropathy Characteristics in Children with Cochlear Nerve Deficiency

Abstract: Children with cochlear nerve deficiency can present with electrophysiologic evidence of AN. These children frequently refer on newborn screening examinations that use ABR-based testing methods. Similar to other causes of AN, diagnostic ABR testing will show a CM with absent neural responses. Given that 9 (18%) of 51 children with available MRI and electrophysiologic characteristics of AN in our program have been identified as having cochlear nerve deficiency makes this a relatively common diagnosis. These find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
142
2
5

Year Published

2009
2009
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(157 citation statements)
references
References 37 publications
8
142
2
5
Order By: Relevance
“…Another study found that 70% of the ears with absent cochlear nerves demonstrated cochlear microphonics, which implies that hair cell functions can persist despite the absence of the cochlear nerve. 7 Another study also documented that normal hair cell development can occur in the absence of innervation. 8 Conversely, the development of spiral ganglion cells and the innervation of the inner ears are dependent on the neurotrophic factors secreted by hair cells.…”
mentioning
confidence: 99%
“…Another study found that 70% of the ears with absent cochlear nerves demonstrated cochlear microphonics, which implies that hair cell functions can persist despite the absence of the cochlear nerve. 7 Another study also documented that normal hair cell development can occur in the absence of innervation. 8 Conversely, the development of spiral ganglion cells and the innervation of the inner ears are dependent on the neurotrophic factors secreted by hair cells.…”
mentioning
confidence: 99%
“…It is important to highlight that both studies we have conducted included only those individuals with normal MRI scans, indicating no structural abnormality of the auditory nerve (although it is acknowledged that even high resolution MRI cannot identify all structural abnormalities). Previous studies have shown that individuals with a known lesion on the auditory nerve (which would also be defined as a post-synaptic or neural lesion) including neural demyelination (Miyamoto et al, 1999) and auditory nerve agenesis or hypoplasia (Maxwell et al, 1999;Gray et al, 1998;Buchman et al 2006) have significantly poorer outcomes following cochlear implantation. While some authors strongly pursue the differentiation of terminology for a true neuropathy of the auditory nerve and an endocochlear disruption that produces the same clinical results , the more inclusive term of ANSD seems to be generally used within the literature.…”
Section: Role Of Evoked Potentials In Decision-makingmentioning
confidence: 99%
“…In this study, 3 patterns were identified: (i) presence of the SP without a CAP, consistent with a pre-synaptic lesion; (ii) presence of the SP and CAP, consistent with a postsynaptic lesion and (iii) significantly prolonged latency potentials (up to 12 ms), which the authors suggest may result from slowed neural conduction and/or reduced action potential generation. Since implantation in cases of cochlear nerve deficiency is known to have poorer outcomes (Buchman et al, 2006), then ECochG provides a useful tool in the differential diagnosis of ANSD. Fig.…”
Section: Role Of Evoked Potentials In Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in MR imaging technology, including high-field-strength units, improved coil technology, and parallel imaging, also allow increasingly highresolution images of the inner ear and brain. [7][8][9][10] High-resolution temporal bone CT is better for assessing bone detail and can be performed at lower cost and in less time, resulting in less frequent need for sedation or anesthesia compared with MR imaging. 6,10 At our institution, MR imaging is the preferred initial imaging test performed in children with newly diagnosed SNHL.…”
Section: Work-up Of Childhood Hearing Loss and Choice Of Imaging Techmentioning
confidence: 99%